PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSETS, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE TAHUN 2018 – 2021 - Vicram Ramadhan; Nur Azizah; Nur Shakinah; Dwi Susilowati; Nadi Hernadi Moorcy; Juwari Juwari (MEDIA RISET EKONOMI [MR.EKO], 2023)
The purpose of this study is to determine the Effect of of Current Ratio, Debt To Equity Ratio (DER), Return On Assets (ROA) and Company Size,on Tax Avoidance in Manufacturing Companies both simultaneously and partially. The population in this study is Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021, namely 193 companies. The study sample amounted to 55 or 220 data selected using the purposive sampling method. The data used is secondary data derived from the annual financial statements of manufacturing companies through the official website of the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The analysis tool uses IBM SPSS statistical version 26. Regression analysis models are multiple linear regression analyses. The results showed that the variables of Current Ratio, Debt To Equity Ratio (DER), Return On Assets (ROA) and Company Size influenced Tax Avoidance.